Frequency, Clinical Presentation and Immediate Outcome of Hypernatraemic Dehydration in Children with Acute Diarrhoea (Bangladesh Journal of Child Health, 2016)
Background: Diarrhoea is a leading cause of illness & death among children in developing countries. Hypernatraemia is a serious complication in acute diarrhoea. It is usually associated with high case fatality rate.Objective: This study, was undertaken to measure the frequency of hypernatraemia, its clinical presentation and the immediate outcome of the problem in Specialized Paediatric Hospital settings.Methods: This was cross sectional observational study. A total of hundred and seven children with acute diarrhoea aged between 2 months to 60 months of both sex admitted in the inpatient department of Dhaka Shishu Hospital and ICH and SSF Hospital, Mirpur-2, over a period of 6 months from August 2011 to February 2012 were included randomly in the study. Serum electrolytes was checked in all the study children just after admission before starting any treatment and at 24 and 72 hours after admission.Results: Among 107 children, hypernatraemia accounted for 12(11.2%) of children. Patients who developed hypernatraemia 4(33.3%) were mild, 5(41.7%) moderate and 3(25%) severely hypernatraemic. The proportion of children with consciousness at baseline and after 24 hours was staggeringly lower in severe hypernatraemic children than that in mild and moderate children. Intact sensory function was found in all mild &severe hypernatraemic children at baseline. Twenty percent of moderate hypernatraemic children had paresthesia at baseline and another 20% after 72 hours, while 33.3% of severe hypernatraemic patients exhibited after 24 hours. All of the patients had signs of severe dehydration at baseline in the three groups. Forty percent of moderate and 33.3% of severe hypernatraemic children had some signs of dehydration after 24 hours and 50% of mild, 40% of moderate and 66.7% of severe hypernatraemic patients after 72 hours. All of the mild and moderate and 1(33.3%) in severe hypernatraemic children improve after treatment and 2(66.7%) of 3 severe hypernatraemic children died during treatment.Conclusion: Hypernatremia is a serious complication of acute diarrhoea in children, which is associated with increased mortality.Bangladesh J Child Health 2015; VOL 39 (1) :18-23